Pengaruh Manajemen Penyaluran Dan Pendampingan Terhadap Peningkatan Pendapatan Pada Program Zakat Produktif - Riskiah; Kurniawan, Heru (Tamaddun Ummah (JTU), 2017)
An increase in income is an increase in the economic benefits of the company's main business or the sale of goods for service obligations received during a certain period.This study uses a quantitative method approach, the data used are primary data obtained through distributing questionnaires to 44 respondents. Data analysis uses multiple regression analysis with the help of SPPS 16.0 windows software. The results showed that the Management of Distribution and Assistance had a positive and significant effect on the Increase of Mustahik's Income at Baznas Dumai City with a contribution of 90.8%, partially assistance contributed greater to the Mustahik Income Increase Productive Zakat Program at BAZNAS Dumai City.